The Relationship of Sphingosine Kinase 1 With Pyroptosis Provides a New Strategy for Tumor Therapy - Wang, Xianwang; Yang, Yue; Cai, Wen-Qi; Lu, Yingying (Frontiers in Immunology, 2020)
Sphingosine kinase 1 (SPHK1) is a crucial molecule that catalyzes sphingosine to synthesize sphingosine-1-phosphate (S1P), facilitating cell survival signaling. Pyroptosis is a perplexing inflammatory mode of cell death primarily triggered by caspase-1, evoked by the NLRP3 inflammasome. Sphingosine is identified as a danger-associated molecular pattern (DAMP), which activates the NLRP3 inflammasome assembly and induces the pyroptosis. It has been demonstrated that macrophages play a pro-tumorigenic role and are closely associated with tumor progression. Attenuation of SPHK1 activity contributes significantly to macrophage pyroptosis and tumor inhibition. Besides, calcium and integrin-binding protein 1 (CIB1) plays an important role in the translocation of SPHK1 from the cytoplasm to the plasma membrane, whereas CIB2 blocks the subcellular trafficking of SPHK1. Therefore, knockout of CIB1 or over-expression of CIB2 will result in sphingosine accumulation and contribute significantly to cancer treatment by several approaches. First, it directly provokes cancer cell apoptosis or triggers robust anti-tumor immunity by pyroptosis-induced inflammation; Second, it could restrain SPHK1 translocation from the cytoplasm to the plasma membrane and further pyroptosis, which not only drive M2 macrophages death but also facilitate tumor microenvironment inflammation as well as the further release of sphingosine from damaged macrophages. The perspective might provide novel insight into the association between SPHK1 and pyroptosis, and suggest the potential target for cancer therapy.